Estudio fitoquímico y capacidad antioxidante in vitro del fruto fresco de jaltomata ventricosa - Gaspar Trebejo, Kelly Jamelli (2015)
The objective of this research was to determine the fresh fruit phytoconstituents Jaltomata ventricosa (Sogorome) and evaluate its antioxidant capacity and determine the concentration of total phenolics and ascorbic acid in this fruit. For the phytochemical study method Martínez and Cuellar, whereby the sample was subjected to the extractive action of solvents of increasing polarity followed dichloromethane, ethanol and water. The concentration of total polyphenols was determined by the Folin-Ciocalteu and ascorbic acid by the method of Robinson Stock using 2,6-dichlorophenolindophenol. The antioxidant capacity was determined by the method of bleaching radical 2,2-diphenyl-1-picrilhidrazilo (DPPH*). The results showed lipids, triterpenes and steroids, catechins, phenolic compounds, flavonoids, anthocyanins, tannins, reducing sugars, amino acids, alkaloids and mucilages as fruit phytoconstituents study. Fresh fruit of Jaltomata ventricosa (Sogorome) presents 319.26 mg gallic acid equivalents per gram of sample and 9.23 mg of ascorbic acid per 100 g of sample. Also this fruit has antioxidant capacity compared with 2, 2-diphenyl-1-picrylhydrazyl, at the dose of 50, 100 and 200 ug / mL (p <0.05), reaching 95.79% at a concentration of 200 ug / mL, with Coefficient of 50% inhibition of 42.51 ug / mL. In conclusion, the fruit is rich in Jaltomata ventricosa (Sogorome) phytoconstituents, I was found high in phenolic compounds and has a moderate antioxidant potential, which would be recommended for consumption